Harnessing lignocellulosic biomass for butanol production through clostridia for sustainable waste management: recent advances and perspectives - Palaniswamy, Sampathkumar; Ashoor, Selim; Eskasalam, Syafira Rizqi; Jang, Yu-Sin (Frontiers in Bioengineering and Biotechnology, 2023)
The escalating waste generation rates, driven by population growth, urbanization, and consumption patterns, have made waste management a critical global concern with significant environmental, social, and economic repercussions. Among the various waste sources, lignocellulosic biomass represents a significant proportion of agricultural, agro-industrial, and municipal wastes. Biofuels are gaining attention as a promising substitute to fossil fuels, and butanol is one such biofuel that has been identified as a potential candidate due to its compatibility with existing fuel infrastructure, lower volatility, and higher energy density. Sustainable management of lignocellulosic biomass waste and its utilization in fermentation are viable alternatives to produce butanol via the promising microbial catalyst clostridia. This review provides an overview of lignocellulosic biomass waste management, focusing on recent advances in strain development for butanol production from renewable biomass with an emphasis on future perspectives.